Symmetry breaking of graphene monolayers by molecular decoration - Dong, Xiaochen (2011)
Aromatic molecules can effectively exfoliate graphite into graphene monolayers, and the resulting graphene monolayers sandwiched by the aromatic molecules exhibit a pronounced Raman G-band splitting, similar to that observed in single-walled carbon nanotubes. Raman measurements and calculations based on the force-constant model demonstrate that the absorbed aromatic molecules are responsible for the G-band splitting by removing the energy degeneracy of in-plane longitudinal and transverse optical phonons at the Γ point.